Síntese da zeólita Beta usando planejamento experimental e emprego na isomerização do n-hexano - Oliveira, Kátia Dionísio de (Universidade Federal de São Carlos, 2012)
This work aimed to apply the Design Of Experiment (DOE) methodology as an auxiliary tool to evaluate the conditions of synthesis of the aluminum-rich zeolite Beta. Bimetallic catalysts with 50% platinum and 50% nickel (50Pt50Ni) supported on zeolites with various Si/Al ratios were synthesized, characterized and evaluated in the isomerization of n-hexane. In the first part of this work, five variables related to the synthesis of zeolite Beta were evaluated by a series of statistical designs, in which the response variables were the relative intensities of the X-ray patterns and the yield of phase BEA. The results of the t-test showed that the ratio TEAOH/SiO2 is not significant for the formation and crystallization of zeolite Beta. However, the interaction of this variable with the Si/Al ratio was statistically significant. In order to obtain the aluminum-rich zeolite Beta, the samples were synthesized with partial substitution of cations TEA+ by cations Na+. The XRD patterns of these samples showed that BEA phase was formed using a Si/Al ratio of 5,0 and 7.5. These low values of Si/Al ratio were confirmed by inductively coupled plasma atomic emission spectroscopy (ICP-AES) and energy-dispersive X-ray spectroscopy (EDS). Information about the main properties of the 50Pt50Ni catalysts such as activity, conversion and selectivity to di-branched isomers in the isomerization of n-hexane were obtained by performing catalytic tests. Concerning these properties, the catalysts supported on the synthesized zeolite Beta (Si/Al = 7.5) showed better catalytic performance compared with catalysts supported on commercial zeolite Beta (Si/Al = 9.0). Additionally to these tests, a study on the kinetics of reduction of ions Pt2+ and Ni2+ on these catalysts was conducted using X-ray absorption spectroscopy (XAS). The combination of XAS analysis and catalytic tests showed the importance of maintaining a bimetallic platinum and nickel system in order to obtain satisfactory performance of catalysts applied to the isomerization of n-hexane. The XAS results suggested that Pt2+ ions are reduced in lower temperatures compared to Ni2+ ions, and that the addition of platinum to the nickel-based samples promoted the reduction of Ni2+ ions. The catalytic results suggested that equilibrium between acid and metal sites exists during the isomerization of n-hexane. The understanding of this equilibrium is of major importance to increase the yield and selectivity to di-branched isomers.
Synthesis of Beta zeolite using experimental design and application in isomerization of n-hexane
Keywords: Planejamento Experimental; Síntese da Zeólita Beta; Alumínio; Isomerização do n-Hexano; Design of experiment; Synthesis of zeolite Beta; Aluminum; Isomerization of n-Hexane; ENGENHARIAS::ENGENHARIA QUIMICA::PROCESSOS INDUSTRIAIS DE ENGENHARIA QUIMICA